Super pulsed thulium fiber laser outcomes in retrograde intrarenal surgery for ureteral and renal stones: a systematic review and meta-analysis - Nazal A. Almasoud; Omar Safar; Adel Elatreisy; Saad Thamer Alshahrani; Saud Bin Libdah; Sulaiman M. Alkhaldi; Nezar F. Alsoliman; Abdulrahman M. Alderaan; Ibrahim Abdel-Al; Tamer A. Abouelgreed; Mohammed Alabeedi; Abdulrahman Al-Aown (BMC Urology, 2023)
Abstract Background Laser lithotripsy using a thulium fiber laser (TFL) has become an effective treatment option for small renal stones with low complication rates. TFL has a higher absorption coefficient, smaller fibers, and better pulse rate capability. Methods We conducted a systematic review and meta-analysis to evaluate the published evidence regarding TFL's lithotripsy performance in retrograde intrarenal surgery (RIRS), for which we primarily assessed the outcomes of stone-free rate, operation time, and complications. We searched different databases from inception to April 2023. We assessed the methodological quality and risk of bias using the Cochrane Risk of Bias tool for randomized trials and the ROBINS-I tool for non-randomized studies. We used a random-effects model for meta-analysis and assessed heterogeneity using the I2 statistic. Results Twelve published studies evaluated the efficacy of RIRS using a TFL for treating renal and ureteral stones. The meta-analysis revealed a predicted stone-free rate of 89.37% (95% CI: 83.93% to 93.12%), indicating that, on average, approximately 89.37% of patients achieved a stone-free state after treatment. The substantial heterogeneity among the studies was evident, as shown by a Q-value of 33.1174 and a p-value of 0.0003. The I2 value of 69.80% (95% CI: 25.91% to 92.02%) highlighted the proportion of variability attributed to genuine heterogeneity across the studies. Moreover, the H2 value 3.31 (95% CI: 1.35 to 12.53) indicated significant heterogeneity beyond random chance. The estimated overall effect size (logit-transformed) of 2.1289 was highly statistically significant (z = 8.7648, p < 0.0001) with a confidence interval of 1.6528 to 2.6049. The reported complications varied across studies, encompassing Clavien grade I–II complications in most cases, with a subset experiencing more severe Clavien grade III–V complications. Additionally, other studies noted a range of complications, such as haematuria, fever, transient creatinine elevation, and postoperative issues like bleeding, pain, and sepsis. Conclusion This meta-analysis suggests that RIRS using TFL is an effective and safe treatment option for renal and ureteral stones, with high stone-free and low complication rates. The included studies exhibited a low risk of bias and were of high quality. However, more extensive randomized controlled trials with extended follow-up periods are needed to investigate this technique's efficacy and safety.